PERLINDUNGAN HUKUM BAGI PENYANDANG CACAT MENTAL SEBAGAI KORBAN TINDAK PIDANA - Mukhti Mukhti (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Whereas the legal arrangement that regulates the implementation of legal protection for persons with mental disabilities as victims of criminal acts is Law Number 19 of 2011 concerning Ratification of the Rights of Persons with Disabilities, persons with disabilities are people who have physical, mental, intellectual or sensory limitations for a long time in interacting with the environment and attitudes of the people may encounter obstacles that make it difficult to participate fully and effectively based on equal rights. The implementation of examinations for persons with mental disabilities as victims of criminal acts is through 4 forms of protection, namely by implementing law enforcement, educative prevention, preventive management, and repressive management. Therefore it is necessary for the Office of Social Affairs and Labor to conduct training and allocate budget funds to ensure legal protection for persons with disabilities who are victims of criminal acts.